The Role of the Respiratory Mucosal Immunity in Protection against Pasteurella Haemolytica A2 Infection in Goats - Abd. Wahid, Mohd. Effendy (1998)

(untitled)
Pneumonic pasteurellosis is one of the most important and devastating diseases in sheep and goats, causing great economic losses to small ruminant industry worldwide. The disease is caused either by Pasteurella haemolytica or Pasteurella multocida and Pasteurella haemolytica A2 is the most common isolate from sheep and goats in Malaysia, comprising approximately 38 per cent of the isolates from pneumonic lung lesions. The disease is best controlled by vaccination, and systemic vaccination has been used for years with limited success. Stress, improper vaccination program and unpopularity of the vaccine among the farmers are some of the reasons that have been associated with the persistence of the disease. Since the systemic vaccination failed to give promising results, studies on the role of mucosal immunity of the respiratory tract in controlling pneumonic pasteurellosis should timely be reviewed. In this study, the bronchus-associated lymphoid tissue (SALT) in the lungs 9 been successfully stimulated by double intranasal exposures to either live or formalin-killed Pasteurella haemolytica A2 at two weeks interval. The size of SALT and number of lymphocytes in the SALT were significantly increased as early as week 2 post-exposure and remained high until week 4 post-exposure. At the same time, the level of IgA against Pasteurella haemolytica A2 increased significantly as early as week 1 post-first exposure and reached a peak level at week 6 post-exposure. The IgM appeared to be present for a short while, at week 3 post-exposure before the levels started to decline in the following week. Initially, the IgG increased gradually and insignificantly before it reached significantly high level at week 4 post-exposure, and remained high at weeks 5 and 6 at the time when the numbers of SALT continued to increase. This study also revealed that intranasal stimulation of SALT was able to protect the lungs from colonization by Pasteurella haemolytica A2 during an in vitro study, thus prevent the lung surface from being adhered and invaded by the organism. However, dexamethasone treatment which is similar to the effect of steroid released under stressful conditions, significantly reduced the number and size of the SALT, thus significantly reduced the percentage of IgA-producing cells. Vaccination trial on goat farm using the pasteurella spray vaccine intranasally showed good protection towards pneumonic pasteurellosis. Significant high levels of systemic antibody responses were also noted during the period of vaccination trial. The incidence of pneumonic pasteurellosis in the farm was markedly reduced.